Homiletics: History and Theology of the Ministry of Preaching in the Church with Contemporary Communication Skills - Fernandes, Cleophas D. (Asian Horizons, 2014)
Joseph Lionel, Homiletics: History and Theology of the Ministry of Preaching in the Church with Contemporary Communication Skills [Foreword by His Eminence Oswald Cardinal Gracias, Archbishop of Bombay], Vatican City: Libreria Editrice Vaticana, 2014. Pages: xviii + 130. ISBN: 978-88-209-9262-0